Facilitating Children's Informal Disclosures of Sexual Abuse: The Role of Online Counsellors at a National Children's Helpline. Issue 3 (3rd April 2022) - Larner, Samuel
ABSTRACT: The literature on disclosures of child sexual abuse makes clear that in the absence of physical indicators of abuse, children need to articulate their abuse in order to prevent further harm. However, many struggle to verbalize their abuse. Previous research has recognized the interactional nature of disclosures but has focussed only on what the children say, rather than considering the role of the other interlocutor. To provide a novel perspective on disclosures, this research addresses the question 'To what extent do counselors facilitate children's disclosures of sexual abuse?' Online text-based conversations in which sexual abuse was disclosed (n = 40) between children (aged 10–18 years old) and Childline counselors were analyzed. Whilst some children do use explicit terms to describe sexual abuse, these are predominantly used to seek definitions and clarification. Furthermore, counselors play an instrumental role in recognizing that a disclosure is being made, and then eliciting and reframing the disclosure as sexual abuse. The findings offer an explanation for why some victims of sexual abuse report having attempted to disclose but feeling like their voices were not heard.